2019
DOI: 10.1128/mbio.02307-19
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic Yeasts Inhibit Virulence of Non -albicans Candida Species

Abstract: Systemic infections of Candida species pose a significant threat to public health. Toxicity associated with current therapies and emergence of resistant strains present major therapeutic challenges. Here, we report exploitation of the probiotic properties of two novel, food-derived yeasts, Saccharomyces cerevisiae (strain KTP) and Issatchenkia occidentalis (strain ApC), as an alternative approach to combat widespread opportunistic fungal infections. Both yeasts inhibit virulence traits such as adhesion, filame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 49 publications
1
58
0
Order By: Relevance
“…This will enable us to determine whether C. auris synergises or is antagonized by co-colonising microorganisms. This may form a platform for alternative bio-control opportunities as suggested by recent probiotic studies [74].…”
Section: Resultsmentioning
confidence: 99%
“…This will enable us to determine whether C. auris synergises or is antagonized by co-colonising microorganisms. This may form a platform for alternative bio-control opportunities as suggested by recent probiotic studies [74].…”
Section: Resultsmentioning
confidence: 99%
“…Due to these characteristics they provide a considerable advantage over bacterial-origin probiotics. Although many yeast species have been shown to possess the characteristics of a probiotic, such as Kluyveromyces lodderae, Kluyveromyces marxianus (Kumura et al, 2004), Kluyveromyces lactis, Yarrowia lipolytica (Li-Shui et al, 2010), and Issatchenkia occidentalis (Kunyeit et al, 2019). Saccharomyces boulardii and Saccharomyces cerevisiae undoubtedly display the most probiotic properties.…”
Section: Yeast-based Probiotics As a Novel Therapeutic Approachmentioning
confidence: 99%
“…Many studies have, also, highlighted the beneficial effects of several S. cerevisiae strains on entheropatogenic bacteria (Martins et al, 2005;Perez-Sotelo et al, 2005;Martins et al, 2007;Etienne-Mesmin et al, 2011;Tiago et al, 2012;Sivignon et al, 2015;Roussel et al, 2018), on inflammatory bowel diseases (Pineton de Chambrun et al, 2015;Tiago et al, 2015;Spiller et al, 2016;Cayzeele-Decherf et al, 2017b;Gayathri et al, 2020), and on pathogenic fungi (C. albicans and non-albicans Candida species, Aspergillus flavus; Premanathan et al, 2011;Abdel-Kareem et al, 2019;Kunyeit et al, 2019;Roselletti et al, 2019b). The potential mechanisms described include: inhibition of pathogen growth (Etienne-Mesmin et al, 2011;Roussel et al, 2018;Abdel-Kareem et al, 2019;Roselletti et al, 2019b), inhibition of pathogen adherence to epithelial cells (Perez-Sotelo et al, 2005;Tiago et al, 2012;Sivignon et al, 2015;Roussel et al, 2018;Kunyeit et al, 2019), immunomodulatory activity (Martins et al, 2005;Martins et al, 2007;Sivignon et al, 2015;Tiago et al, 2015;Roussel et al, 2018;Roselletti et al, 2019b), inhibition of filamentation and biofilm development (Kunyeit et al, 2019), and reduction of toxin production (Roussel et al, 2018;Abdel-Kareem et al, 2019).…”
Section: Yeast-based Probiotics As a Novel Therapeutic Approachmentioning
confidence: 99%
“…C. albicans must first adhere to abiotic surfaces then filament to form a three-dimensional biofilm. Beneficial yeast cell number 10 8 / ml was empirically determined as effective against adhesion of C. albicans SC5314 (Kunyeit et al, 2019). To test the effect of the two food derived yeasts Saccharomyces cerevisiae and Issatchenkia occidentalis (Archana and Anu-Appaiah, 2018) on C. albicans virulence we tested adhesion, filamentation and biofilm formation in vitro.…”
Section: Food Derived Yeasts Inhibit Virulence Traits Of Candida Albimentioning
confidence: 99%
“…boulardii and S. cerevisiae have been shown to prevent the colonization and virulence of C. albicans (Pericolini et al, 2017, Murzyn et al, 2010, Jawhara and Poulain, 2007. We and others have previously reported that secreted factors from food-derived beneficial yeasts inhibited virulence traits of many pathogenic fungi (Kunyeit et al, 2019, Banjara et al, 2016. These food-derived yeasts have been considered beneficial in many cultural settings, yet their molecular mechanism of action has not been identified.…”
Section: Introductionmentioning
confidence: 99%